PENERAPAN QUIZIZZ PAPER-MODE TERHADAP HASIL BELAJAR PADA MATA PELAJARAN GEOGRAFI SISWA FASE E DI SMA NEGERI 1 SAROLANGUN - Alisa Chanaya; Loli Setriani; Nefilinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the limited use of interactive learning media in the learning process, which results in low student motivation and difficulties in understanding the subject matter. Many students' learning outcomes fall below the Minimum Mastery Criteria (KKTP) of 75 at SMA Negeri 1 Sarolangun. The aim of this study is to examine the effect of applying Quizizz Paper-Mode on Geography learning outcomes of Phase E students at SMA Negeri 1 Sarolangun. This research employs a quantitative approach with the population consisting of Phase E students in the 2024/2025 academic year. Class E.10 was assigned as the control group, and class E.9 as the experimental group. Data analysis techniques used include descriptive statistics and correlation tests. The results show that the average score of the control class is 81.51, while the experimental class reaches 84.31. The t-test results in a significance value of 0.000 < 0.05, indicating that the alternative hypothesis (Hₐ) is accepted and the null hypothesis (H₀) is rejected. It can be concluded that the use of Quizizz Paper-Mode has a significant influence on the Geography learning outcomes of Phase E students at SMA Negeri 1 Sarolangun.